2005
DOI: 10.1177/154405910508400905
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Delivery and Other Maternal Factors Influence the Acquisition of Streptococcus mutans in Infants

Abstract: S. mutans plays a key role in dental caries. The extent to which perinatal events influence the acquisition of S. mutans is unclear. We hypothesized that several maternal factors, including the mode of delivery, influence the initial acquisition of S. mutans in infants. A prospective cohort study was conducted in 156 mother-infant pairs. The study found that maternal gestational age (p = 0.04), S. mutans level (p = 0.02), caries score (p = 0.02), sexually transmitted disease (STD) infection experience (p = 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
152
7
13

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(181 citation statements)
references
References 25 publications
9
152
7
13
Order By: Relevance
“…Questions concerning pre-term birth and/or vaginal/cesarean-section birth of the child were added at the one-year visit, because it had been suggested that cesarean-section-delivered children acquired S. mutans earlier (Li et al, 2005), and early Odds Ratio (with 95% CI) for All Children (n = 329) Figure 3. Odds ratios with 95% confidence intervals for dietary habits for prediction of at least 1 new ICDAS score of 3 or higher, at least 1 new filling, and/or at least 1 previous lesion progressing from a 3 or 4 to a 5 or 6 for all children.…”
Section: Discussionmentioning
confidence: 99%
“…Questions concerning pre-term birth and/or vaginal/cesarean-section birth of the child were added at the one-year visit, because it had been suggested that cesarean-section-delivered children acquired S. mutans earlier (Li et al, 2005), and early Odds Ratio (with 95% CI) for All Children (n = 329) Figure 3. Odds ratios with 95% confidence intervals for dietary habits for prediction of at least 1 new ICDAS score of 3 or higher, at least 1 new filling, and/or at least 1 previous lesion progressing from a 3 or 4 to a 5 or 6 for all children.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure that co-exists with an increased probability of developing a disease is known as risk indicator [128].…”
Section: Risk Indicatormentioning
confidence: 99%
“…Li et al (2005) reported that children of Caesarean delivery acquired MS significantly earlier than those of vaginal delivery. In this study, however, the mode of delivery did not affect caries occurrence.…”
Section: Discussionmentioning
confidence: 99%